(untitled) (Journal of Medicine, 2015)
Hoffman syndrome is characterized by pseudohypertrophy of muscles, muscles weakness & stiffness complicating hypothyroidism. We describe the disorder in a 45 years old female admitted with complaints of myalgia, proximal muscle weakness & calf muscle hypertrophy since 11 months. Thyroid function tests, marked elevation of muscle enzyme, electromyogram & muscle biopsy established the diagnosis of thyroid myopathy with Hoffmans syndrome. Therapy with levothyroxine resulted in marked clinical & biochemical improvements. J MEDICINE July 2015; 16 (2) : 112-114